Microencapsulation of Caramel Flavor and Properties of Ready-to-drink Milk Beverages Supplemented with Coffee Containing These Microcapsules - Kim, Gur-Yoo; Lee, Jaehak; Lim, Seungtae; Kang, Hyojin; Ahn, Sung-Il; Jhoo, Jin-Woo; Ra, Chang-Six (Food science of animal resources, 2019)
This study aimed to extend the retention of flavor in coffee-containing milk beverage by microencapsulation. The core material was caramel flavor, and the primary and secondary coating materials were medium-chain triglyceride and maltodextrin, respectively. Polyglycerol polyricinoleate was used as the primary emulsifier, and the secondary emulsifier was polyoxyethylene sorbitan monolaurate. Response surface methodology was employed to determine optimum microencapsulation conditions, and headspace solid-phase microextraction was used to detect the caramel flavor during storage. The microencapsulation yield of the caramel flavor increased as the ratio of primary to secondary coating material increased. The optimum ratio of core to primary coating material for the water-in-oil (W/O) phase was 1:9, and that of the W/O phase to the secondary coating material was also 1:9. Microencapsulation yield was observed to be approximately 93.43%. In case of in vitro release behavior, the release rate of the capsules in the simulated gastric environment was feeble; however, the release rate in the simulated intestinal environment rapidly increased within 30 min, and nearly 70% of the core material was released within 120 min. The caramel flavor-supplemented beverage sample exhibited an exponential degradation in its flavor components. However, microcapsules containing flavor samples showed sustained flavor release compared to caramel flavor-filled samples under higher storage temperatures. In conclusion, the addition of coffee flavor microcapsules to coffee-containing milk beverages effectively extended the retention of the coffee flavor during the storage period.This study aimed to extend the retention of flavor in coffee-containing milk beverage by microencapsulation. The core material was caramel flavor, and the primary and secondary coating materials were medium-chain triglyceride and maltodextrin, respectively. Polyglycerol polyricinoleate was used as the primary emulsifier, and the secondary emulsifier was polyoxyethylene sorbitan monolaurate. Response surface methodology was employed to determine optimum microencapsulation conditions, and headspace solid-phase microextraction was used to detect the caramel flavor during storage. The microencapsulation yield of the caramel flavor increased as the ratio of primary to secondary coating material increased. The optimum ratio of core to primary coating material for the water-in-oil (W/O) phase was 1:9, and that of the W/O phase to the secondary coating material was also 1:9. Microencapsulation yield was observed to be approximately 93.43%. In case of in vitro release behavior, the release rate of the capsules in the simulated gastric environment was feeble; however, the release rate in the simulated intestinal environment rapidly increased within 30 min, and nearly 70% of the core material was released within 120 min. The caramel flavor-supplemented beverage sample exhibited an exponential degradation in its flavor components. However, microcapsules containing flavor samples showed sustained flavor release compared to caramel flavor-filled samples under higher storage temperatures. In conclusion, the addition of coffee flavor microcapsules to coffee-containing milk beverages effectively extended the retention of the coffee flavor during the storage period.